2022
DOI: 10.1186/s40001-022-00798-6
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocephalus: historical analysis and considerations for treatment

Abstract: Hydrocephalus is a serious condition that affects patients of all ages, resulting from a multitude of causes. While the etiologies of hydrocephalus are numerous, many of the acute and chronic symptoms of the condition are shared. These symptoms include disorientation and pain (headaches), cognitive and developmental changes, vision and sleep disturbances, and gait abnormalities. This collective group of symptoms combined with the effectiveness of CSF diversion as a surgical intervention for many types of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 114 publications
(158 reference statements)
0
32
0
Order By: Relevance
“…A few patients with idiopathic hydrocephalus also have this situation. However, patients with such hydrocephalus often need to be checked for improved CSF indicators through repeated lumbar punctures, external lumbar cistern drainage, and external lateral ventricle drainage, among other, thus missing the best time for operation, ultimately delaying or even aggravating the condition ( 2 , 13 , 14 ). Rammos et al ( 15 ) reported that the average time for external ventricular drainage before the conversion to internal drainage was 14.1 days, though this could sometime last as long as 45 days.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A few patients with idiopathic hydrocephalus also have this situation. However, patients with such hydrocephalus often need to be checked for improved CSF indicators through repeated lumbar punctures, external lumbar cistern drainage, and external lateral ventricle drainage, among other, thus missing the best time for operation, ultimately delaying or even aggravating the condition ( 2 , 13 , 14 ). Rammos et al ( 15 ) reported that the average time for external ventricular drainage before the conversion to internal drainage was 14.1 days, though this could sometime last as long as 45 days.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrocephalus refers to the imbalance between cerebrospinal fluid (CSF) production and absorption, and/or the obstruction of its pathways, resulting in disturbed CSF dynamics and the abnormal accumulation of excess CSF in either the ventricle or subarachnoid space, which then dilatates these areas ( 1 , 2 ). Hydrocephalus commonly occurs in neurosurgical patients ranging from newborns to adults.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inclusion criteria: x History of DC; y hydrocephalus diagnosed by CT or MRI (15)(16)(17); (Evan's index >0.3, or associated with periventricular interstitial edema; Other causes of ventricular enlargement were excluded. z The presence of hydrocephalusrelated symptoms, such as headache, neurological dysfunction, etc., normal pressure hydrocephalus contains at least one of the following symptoms: gait disorders, cognitive disorders, urinary incontinence (18)(19)(20). { At least 4 weeks after DC.…”
Section: Methods Patients Selectionmentioning
confidence: 99%
“…Hydrocephalus may be defined as abnormal accumulation of cerebrospinal fluid (CSF) within the ventricles of the brain, leading to ventricular expansion or enlargement and usually associated with raised intracranial pressure [1,2]. Hydrocephalus (HCP) is one of the most common associations of myelomeningocele, and it may be overt and present at birth or be latent and develop following the repair of myelomeningocele.…”
Section: Introductionmentioning
confidence: 99%